Exponential Robust Consensus of Multiagent Systems with Markov Jump Parameters - He Zhang; Huihui Ji; Zhiyong Ye; Tan Senping (Abstract and Applied Analysis)
Exponential robust consensus of stochastic multiagent systems is studied. Coupling structures of multiagent systems are Markov jump switching; that is, multiagent systems contain Markov jump parameters. Sufficient conditions of almost surely exponential robust consensus are derived by utilizing the stochastic method and the approach of the matrix inequality. Finally, two simulations are shown to demonstrate the validity of the achieved theoretical results.